Does Tenascin have Clinical Implications in Pathological Grade of Glioma Patients?. Issue 32 (August 2015) - Kong, Xiangyi; Ma, Wenbin; Li, Yongning; Wang, Yu; Guan, Jian; Gao, Jun; Wei, Junji; Yao, Yong; Lian, Wei; Xu, Zhiqin; Dou, Wanchen; Xing, Bing; et al.
<x xml:space="preserve">Abstract</x> Abstract Tenascin (TN) is an extracellular oligomeric glycoprotein that participates in the adhesion of cells to extracellular matrixc (ECM). Studies have shown that the expression levels of TN are upregulated in a variety of cancers, including colon cancer, lung cancer, brain tumor, and breast cancer. However, the implications and utilities of TN in clinical grading and prognosis of glioma patients were seldom reported and the effects of its pathway are still unclear and controversial. Thus, it is essential to carry out a meta-analysis to draw a convincing conclusion. A literature search was carried out up to April 2015. Data was collected using a purpose-designed form including glioma's WHO grade, etc. Differences were expressed as odds ratios (ORs) or standard mean differences (SMDs) with 95% confidence intervals (CIs). Galbr figure, Cochran's Q test, and I2 test were all performed to judge the heterogeneity between included studies. To examine the stability of the pooled results, a sensitivity analysis was performed. Potential publication bias was assessed by visual inspection of funnel plot. As this meta-analysis, as a systematic review, does not involve animal experiments or direct human trials, there is no need to conduct special ethic review and the ethical approval is not necessary. In this meta-analysis, 8 eligible studies involving 456 patients were incorporated. Six studies with dichotomous data revealed TN overexpression in glioma tissues and/or surrounding neoplastic vessels was closely associated with high WHO grade (III + IV) (odds ratio 3.398, 95% confidence interval 1.933, 5.974; P = 0.000); three continuous data studies showed there were close statistical associations between TN and WHO grade (SMD −2.114, 95% CI −2.580, −1.649; P = 0.000) too. Sensitivity analysis indicated a statistically robust result. No publication bias was revealed. Our meta-analysis suggests that TN expression is potentially associated with higher WHO grade of gliomas. More evidences on the basis of the evidence-based medicine are needed to prove it.